On the choice of an effective strategy and tactics in the early diagnosis, prevention and treatment of open — angle glaucoma (Ukrainian Journal of Ophthalmology, 2026)
On the choice of an effective strategy and tactics in the early diagnosis, prevention and treatment of open — angle glaucoma